Public Health Importance of Invasive Methicillin-sensitive Staphylococcus aureus Infections: Surveillance in 8 US Counties, 2016. (23rd April 2019) - Jackson, Kelly A; Gokhale, Runa H; Nadle, Joelle; Ray, Susan M; Dumyati, Ghinwa; Schaffner, William; Ham, David C; Magill, Shelley S; Lynfield, Ruth; See, Isaac
Abstract: Background: Public health and infection control prevention and surveillance efforts in the United States have primarily focused on methicillin-resistant Staphylococcus aureus (MRSA). We describe the public health importance of methicillin-susceptible S. aureus (MSSA) in selected communities. Methods: We analyzed Emerging Infections Program surveillance data for invasive S. aureus (SA) infections (isolated from a normally sterile body site) in 8 counties in 5 states during 2016. Cases were considered healthcare-associated if culture was obtained >3 days after hospital admission; if associated with dialysis, hospitalization, surgery, or long-term care facility (LTCF) residence within 1 year prior; or if a central venous catheter was present ≤2 days prior. Incidence per 100 000 census population was calculated, and a multivariate logistic regression model with random intercepts was used to compare MSSA risk factors with those of MRSA. Results: Invasive MSSA incidence (31.3/100 000) was 1.8 times higher than MRSA (17.5/100 000). Persons with MSSA were more likely than those with MRSA to have no underlying medical conditions (adjusted odds ratio [aOR], 2.06; 95% confidence interval [CI], 1.26–3.39) and less likely to have prior hospitalization (aOR, 0.70; 95% CI, 0.60–0.82) or LTCF residence (aOR, 0.37; 95% CI, 0.29–0.47). MSSA accounted for 59.7% of healthcare-associated cases and 60.1% of deaths. Conclusions: Although MRSA tended to be more closely associated with healthcare exposures, invasive MSSA is a substantial public health problem in the areas studied. Public health and infection control prevention efforts should consider MSSA prevention in addition to MRSA. Abstract : In population-based invasive Staphylococcus aureus (SA) infection surveillance in five U.S. states, methicilin-susceptible SA (MSSA) incidence was 1.8 times higher than methicillin-resistant SA and accounted for most deaths. Public health and infection control prevention and surveillance priorities should include MSSA.